Arabidopsis Glutaredoxin S17 and Its Partner, the Nuclear Factor Y Subunit C11/Negative Cofactor 2α, Contribute to Maintenance of the Shoot Apical Meristem under Long-Day Photoperiod. Issue 4 (19th February 2015) - Knuesting, Johannes; Riondet, Christophe; Maria, Carlos; Kruse, Inga; Bécuwe, Noëlle; König, Nicolas; Berndt, Carsten; Tourrette, Sébastien; Guilleminot-Montoya, Jocelyne; Herrero, Enrique; Gaymard, Frédéric; Balk, Janneke; et al.
Abstract : An unusual multidomain glutaredoxin and its protein partner affect plant development and flowering time in relation to photoperiod in Arabidopsis. Abstract: Glutaredoxins (GRXs) catalyze the reduction of protein disulfide bonds using glutathione as a reductant. Certain GRXs are able to transfer iron-sulfur clusters to other proteins. To investigate the function of Arabidopsis ( Arabidopsis thaliana ) GRXS17, we applied a strategy combining biochemical, genetic, and physiological approaches. GRXS17 was localized in the nucleus and cytosol, and its expression was elevated in the shoot meristems and reproductive tissues. Recombinant GRXS17 bound Fe2 S2 clusters, a property likely contributing to its ability to complement the defects of a Baker's yeast ( Saccharomyces cerevisiae ) strain lacking the mitochondrial GRX5. However, a grxs17 knockout Arabidopsis mutant exhibited only a minor decrease in the activities of iron-sulfur enzymes, suggesting that its primary function is as a disulfide oxidoreductase. The grxS17 plants were sensitive to high temperatures and long-day photoperiods, resulting in elongated leaves, compromised shoot apical meristem, and delayed bolting. Both environmental conditions applied simultaneously led to a growth arrest. Using affinity chromatography and split-Yellow Fluorescent Protein methods, a nuclear transcriptional regulator, the Nuclear Factor Y Subunit C11/Negative Cofactor 2α (NF-YC11/NC2α), was identified as a GRXS17 interacting partner. A mutant deficient in NF-YC11/NC2α exhibited similar phenotypes to grxs17 in response to photoperiod. Therefore, we propose that GRXS17 interacts with NF-YC11/NC2α to relay a redox signal generated by the photoperiod to maintain meristem function.